Efektivitas kompres hangat jahe merah dan kompres air hangat terhadap penurunan intensitas nyeri pada penderita rheumatoid arthritis - Nora Hayani; Fenti Hasnani; Zulkarnaini Zulkarnaini; Azwarni Azwarni (Jurnal SAGO Gizi dan Kesehatan, 2024)
Background: Rheumatoid Arthritis is a chronic inflammatory disease of the joints that can affect all ages, this disease is more common in women with complaints that are often felt, namely pain, redness, swelling and stiffness in the joints so that they can limit and interfere with daily activities.Objective: The study aims to determine the effectiveness of warm red ginger compresses and warm water compresses on reducing pain intensity in patients with rheumatoid arthritis. Methods: Comparative research using a pre-experimental design, the subjects were rheumatoid patients, the number of respondents was 82 people divided into two groups, namely the red ginger warm compress group 41 respondents and the warm water compress group 41 respondents conducted in the Sungai Iyu Health Center Working Area on May 8 to August 15, 2023. Data collection by performing warm water compress treatment and red ginger warm compress, measuring pain intensity with a numerical rating scale by considering research ethics. Data analysis using Wilcoxon test and mann whitney test at 95% confidence level.Results: Giving warm compresses of red ginger and warm water compresses can reduce pain intensity in patients with rheumatoid arthritis (p = 0,000), and it was found that warm compresses of red ginger were more effective in reducing pain in patients with rheumatoid arthritis (p = 0,003).Conclusion: Warm red ginger compress and warm water compress can reduce pain in rheumatoid arthritis patients, but warm red ginger compress is more effective in reducing pain intensity in rheumatoid arthritis patients.Keywords Red Ginger Compress, Warm Water Compress, Rheumatoid Arthritis